Produção e aplicação de imunoglobulinas y anti-Leptospira spp - Tavares, Tatiane Cristina Fernandes (2012)
The dissertation was divided in two chapters. The aim was to determine whether hens immunized with an inactivated suspension of Leptospira and a solution of outer membrane proteins extracted from the serovar Hardjo, could produce specific polyclonal antibodies to Leptospira, detected in ELISA assay. Eight hens White Leghorn race with 25-weeks-old were immunized, three with an inactivated suspension of Leptospira, three with a solution of outer membrane proteins (OMP) extracted from the serovar Hardjo and two controls immunized with saline. Blood samples were collected fortnightly and eggs daily. The IgY was purified from the egg yolk using the method for the delipidation of dilution with water acidic and ammonium sulfate precipitation. The ELISA assay was performed to verify the specificity of the IgY, these was possible to observe the production of specific antibody to Leptospira both in serum and purified egg yolk. The specific antibody titers peaked in the fifth week post immunization. The production of polyclonal IgY was effective for producing high titers of specific antibodies. The aim of the second chapter was search to epitopes or mimetops (mimetic sequence of the true epitopes) through technique of phage display using IgY specific to Leptospira, outer membrane proteins the serovar Hardjo and IgY control. To realize the biopanning was used a commercial library of random peptides Ph.D. 12 mer, New England BioLabs®Inc Phage Display Library was first incubated with IgY control, performing a process called negative selection, and then with IgY specific to Leptospira and to OMP Leptospira Hardjo, selected phages were eluted competitively and acid. After three rounds of selection, 288 clones were isolated and sequenced, generating 132 valid sequences. The selected clones were tested in diagnosis by ELISA assay with the antibody used as a biopanning target in order to verify the specificity of these. The results of ELISA testing it was found that nine phage (PMEcomp17, PMEac10, PMEac12, PMEac19, PMEac29, PMEac35, Lep6, Lep7 e Lep20) showed better results. These were aligned with the primary sequence of proteins of Leptospira spp. and Leptospira interrogans serovar Hardjo and insilico analyzes showed that nine peptides has similarity with immunogenic proteins of Leptospira. In this work we selected nine peptides with similarity to proteins of Leptospira interrogans that were considered immunogenic. The peptides were similar to outer membrane proteins, lipoprotein, LipL32, LipL41, LigA, SecY, LenE.